The Influence of Quality of Measles Vaccine to The Incidence of Measles in Pasuruan Regency - Ningtyas, Dwi Wahyu; Wibowo, Arief (Faculty of Public Health, 2015)
ABSTRACTThe measles is a major cause of child mortality among vaccine preventable disease. The incidence of measles reach out 198 cases in 2014 at Pasuruan. The incidence of measles in Pasuruan, not only in areas with low immunization coverage but also in areas with high immunization coverage, it may indicate the quality of the vaccines given bad that does not provide protection to measles disease. The aim of this study was to analyze the influence of quality of measles vaccine to the incidence of measles in Pasuruan Regency. This study was an analytic observational with case-control approach. The samples of this study taken 30 villages which had measleas cases in 2014 and 30 villages which had not measles cases in 2014. The data was analyzed by using linier regression and logistic regression. The result of the study confirmed that training (p = 0.002), knowledge (p = 0.000), and the availability of vaccine (p = 0.022) effect on the quality of measles vaccine; thus the quality of measles vaccine (p = 0.008) effect on the incidence of measles. The conclusion of this study the influence of which there are knowledge to the quality of measles vaccine; and there is influence between quality of measles vaccine to the incidence of measles. Suggestions can be drawn based on the results of this study, increase health workers knowledge about the measles immunization coverage and the quality of measles vaccine with mentoring, and require officers to use the facilities and infrastructure of immunization according to SOP (Standard Operating Procedure).Keywords: incidence of measles, quality of measles vaccine